2017
DOI: 10.1186/s12906-017-1698-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperuricemic, Anti-Inflammatory and Analgesic Effects of Siegesbeckia orientalis L. Resulting from the Fraction with High Phenolic Content

Abstract: BackgroundThe medicinal plant Siegesbeckia orientalis L. has been commonly used for the treatment of acute arthritis, rheumatism, and gout in Vietnam. However, pharmacological research of this plant associated with gout has not been reported. Anti-hyperuricemic and anti-inflammatory effects were evaluated and observed for the crude ethanol extract (CEE) of S. orientalis. Retention of these biological properties was found in a n-butanol-soluble fraction (BuOH fr.) of the extract, and therefore further biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 29 publications
2
32
0
6
Order By: Relevance
“…The antihyperuricemic activity of α-LA investigated using the potassium oxonate-induced hyperuricemia in the rat's model according to Haidari et al [25] and Nguyen et al [26] with modifications. Animals were fasted by withdrawing of food and water 2 h before drugs administration.…”
Section: Evaluation Of Antihyperuricemic Activitymentioning
confidence: 99%
“…The antihyperuricemic activity of α-LA investigated using the potassium oxonate-induced hyperuricemia in the rat's model according to Haidari et al [25] and Nguyen et al [26] with modifications. Animals were fasted by withdrawing of food and water 2 h before drugs administration.…”
Section: Evaluation Of Antihyperuricemic Activitymentioning
confidence: 99%
“…In the 2015 edition of Chinese Pharmacopeia, it is recorded that the aerial parts of three Siegesbeckia genus plants Siegesbeckia pubescens Makino, S. orientalis L. and S. glabrescens Makino are used as HS (3). In the clinic, HS is widely prescribed to treat inflammatory diseases such as furuncle, arthritis and gout (4). Some preparations made solely from this herb are commercially available (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have demonstrated that HS possesses anti-inflammatory effects in animal models, such as xylene-induced ear edema in mice; cottonball-induced granuloma (6), collagenase-induced paw edema (7) and urate-induced synovitis in rats (4); as well as rheumatoid arthritis induced by mixed arthrogen monoclonal antibody in mice (8). In vitro studies have shown that HS inhibits inflammatory mediators by suppressing the MAPK-and NF-κB-pathways in LPSstimulated RAW264.7 cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…Its ethanol extract could suppress the growth and metastasis of endometrial cancer cells [ 30 , 31 ]. Additionally, S. orientalis extracts possess significant anti-inflammatory, anti-hyperuricemic and analgesic activities [ 32 , 33 ]. However, to our best knowledge, the effects of S. orientalis extracts on metabolic syndrome, such as Type 2 diabetes-linked hyperglycemia and related cardiovascular complications, have not yet been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%